No evidence that elevated CO 2 gives tropical lianas an advantage over tropical trees - David C. Marvin; Klaus Winter; Robyn J. Burnham; Stefan A. Schnitzer (Global Change Biology, 2015)
Recent studies indicate that lianas are increasing in size and abundance relative to trees in neotropical forests. As a result, forest dynamics and carbon balance may be altered through liana‐induced suppression of tree growth and increases in tree mortality. Increasing atmospheric CO 2 is hypothesized to be responsible for the increase in neotropical lianas, yet no study has directly compared the relative response of tropical lianas and trees to elevated CO 2 . We explicitly tested whether tropical lianas had a larger response to elevated CO 2 than co‐occurring tropical trees and whether seasonal drought alters the response of either growth form. In two experiments conducted in central Panama, one spanning both wet and dry seasons and one restricted to the dry season, we grew liana ( n = 12) and tree ( n = 10) species in open‐top growth chambers maintained at ambient or twice‐ambient CO 2 levels. Seedlings of eight individuals (four lianas, four trees) were grown in the ground in each chamber for at least 3 months during each season. We found that both liana and tree seedlings had a significant and positive response to elevated CO 2 (in biomass, leaf area, leaf mass per area, and photosynthesis), but that the relative response to elevated CO 2 for all variables was not significantly greater for lianas than trees regardless of the season. The lack of differences in the relative response between growth forms does not support the hypothesis that elevated CO 2 is responsible for increasing liana size and abundance across the neotropics.